A Bayesian Approach to an Individual Player's Choice of Bid in Competitive Sealed Auctions - Lavalle, Irving H. (Management Science, 1967)
A general approach to the decision problem confronting the individual player in a noncooperative game is outlined and applied to one player's choice of bid in a competitive sealed auction for a valuable object. That player's Bayes-optimal bid is characterized under both general and specific assumptions as to the subjective probability distributions expressing his judgments. Under the specific assumptions, analytically tractable results (in terms of Gamma fractiles) are presented. Equilibrium and maximin bids are presented for comparative purposes.